Overexpression, purification and crystallization of tyrosyl-tRNA synthetase from the hyperthermophilic archaeon Aeropyrum pernix K1 - Iwaki, Jun (International Union of Crystallography, 2005)
Hyperthermophilic archaeal tyrosyl-tRNA synthetase from Aeropyrum pernix K1 was cloned and overexpressed in Escherichia coli. The expressed protein was purified by Cibacron Blue affinity chromatography following heat treatment at 363 K. Crystals suitable for X-ray diffraction studies were obtained under optimized crystallization conditions in the presence of 1.5 M ammonium sulfate using the hanging-drop vapour-diffusion method. The crystals belonged to the tetragonal space group P4(3)2(1)2, with unit-cell parameters a = b = 66.1, c = 196.2 Å, and diffracted to beyond 2.15 Å resolution at 100 K.